Do You Feel the Same? Different Dominants of Theatrical Experience - Toome, Heli-Liis (Nordic Theatre Studies, 2015)
The aim of this article is to present an exploratory study of reception research of theatrical experiences of general audiences of spoken theatre performances in Tartu, Estonia. The research is based on a quantitative survey of the audiences of eight spoken theatre performances. Factor analysis is used to assemble 24 different performance characteristics into five factors: Aesthetic, Entertainment, Personally Challenging, Complexity and Conventionality Factor. The factor analysis also points out some possible overlaps (characteristics that could be included into different factors at the same time) between factors, particularly between the Aesthetic and Personally Challenging Factor. These overlaps could be explained by (1) the limits of the quantitative survey, (2) the language and (3) the performances included in the survey. The overlaps, from the perspective of the viewer being inspired, challenged and excited by the performance, are due to the reason that the performances are personally touching as well as demanding and are performed by skilful performers. The article discusses the point that aesthetically challenging performances can be thematically or artistically demanding for the viewer, if the viewer has a personal relationship to the theme.